VD_FINDINFO AI 503/09 - 28/2012 vom 19. Dezember 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, DEGRÉ DE L'INCAPACITÉ DE TRAVAIL | 28 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA